Shelf-life prediction of blondo-based probiotic ice cream using accelerated shelf-life testing method - Rafli Zulfa Kamil; Sri Mulyani; Regina Putri Ikhwani; Ana Wulandari (AGROINTEK, 2025)
Blondo is a by-product of VCO production, commonly used for feed despite its rich nutrition and physiological properties. To reutilize blondo and take advantage of its nutrition, blondo probiotic ice cream is developed as a plant-based functional food. Determining the shelf-life of food products is very important because it reflects the product's durability during the time interval between production and consumption. This study aims to determine the shelf-life of blondo-based probiotic ice cream using the Accelerated Shelf-Life Testing (ASLT) method with the Arrhenius model. Blondo-based probiotic ice cream was stored for 28 days at temperatures of -6℃, -11℃, and -18℃. The parameters observed were total Lactic Acid Bacteria (LAB), total acid, pH value, and total solids. The results of the calculation of the Arrhenius model selected the total LAB parameter as a critical parameter. Therefore, we considered using the term “best before” to refer to probiotic efficacy instead of shelf-life. The blondo-based probiotic ice cream is best consumed before if stored at -6℃ is 206.80 days or 6 months 27 days; at -11℃ is 186.47 days or six months 6 days; and at -18℃ is 160.22 days or 5 months 10 days.